Extraction of cable joints tangent delta from bulk tangent delta measurement using HFAC method - Shafi H.; Anthony T.M.; Basri A.; Raj A.; Chakrabarty C. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cable jointing; Dielectric devices; Dielectric losses; Extraction; Insulating materials; Insulation; Standards; Underground cables; Condition assessments; Diagnostic methods; Direct measurement method; Dissipation factors; Extraction method; Insulation conditions; Insulation degradation; Tangent delta; Cables